Trauma traqueal associado à fratura mandibular: relato de caso - Jardim, Ellen Cristina Gaetti; Pereira, Cassiano Costa Silva [UNESP]; Faverani, Leonardo Perez [UNESP]; Manrique, Gustavo Rodrigues; Freitas, Gileade Pereira; Shinohara, Elio Hitoshi [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (My University, 2012)
Introduction: The mandibular injuries account for about 20% to 50% of cases of facial fractures. Some consider the jaw the second most commonly fractured bone of the skull, and is the only mobile bone of the facial framework, which results in decreased stability compared to the trauma. When one takes into account the degree of airway obstruction in patients with facial fractures, the problem becomes much more serious since it is one of the most troubling complications of trauma. Objective: the relevance of the topic is aimed to report a case of a patient victim of mandibular fracture associated with trauma to the trachea. Case report: Case report: Patient 24 years old patient with tracheal trauma concomitant mandibular fracture surgically treated in conjunction with the thoracic surgeon. After 5 months postoperatively, the patient is in good condition general, no complaints. Final comments: This form is observed that the key to proper treatment of tracheal trauma associated with facial fractures is the knowledge of the type of injury, and an accurate diagnosis multidisciplinary.

Introdução: As injúrias mandibulares correspondem a cerca de 20% a 50% dos casos de fraturas faciais. Alguns consideram a mandíbula o segundo osso do crânio mais fraturado, além de ser o único osso móvel do arcabouço facial, o que resulta na diminuição da estabilidade frente ao trauma. Quando se leva em consideração a obstrução de vias aéreas em pacientes com fraturas faciais, a problemática torna-se muito mais grave já que se trata de uma das mais preocupantes complicações em traumatologia. Objetivo: Diante da relevância do tema é objetivo relatar um caso clínico de paciente vítima de fratura mandibular associada a trauma de traqueia. Relato de caso: Paciente de 24 anos de idade portador de trauma traqueal concomitante a fratura mandibular por coice animal tratado cirurgicamente em conjunto ao cirurgião torácico. Após 5 meses de pós-operatório, o paciente encontra-se em bom estado geral, sem queixas. Comentários finais: Desta forma é observado que a chave para o correto tratamento de trauma traqueal associado a fraturas faciais é o conhecimento do tipo de injúria, além de um acurado diagnóstico multidisciplinar.
Tracheal trauma associated with mandibular fracture: case report
Keywords: Trachea; Diagnosis; Mandibular fractures; Fracture fixation; Internal; Traqueia; Diagnóstico; Fraturas mandibulares; Fixação interna de fraturas